Markers of metastatic colorectal cancer - Piotr Myśliwiec; Barbara Choromanska; Jacek Dadan (Gastroenterology Review)
Metastatic colorectal cancer (CRC) is a major cause of cancer-related death. However, early diagnosis of CRC metastases offers a chance of long-term survival in as much as 40% of patients after curative treatment. Current guidelines are based on clinical examination, carcinoembryonic antigen (CEA) testing, computed tomography scanning, and endoscopic surveillance. Although CEA is the most widely used laboratory test, it has very low sensitivity (30–40%). Moreover, there is no evidence to support the association of CEA testing with improved survival or quality of life. Thus, novel markers with greater specificity and sensitivity are needed. The aim of this review was to define the role of available laboratory markers in early diagnosis of metastatic CRC. We identified novel tests with the highest association to metastatic CRC: circulating tumour DNA, growth/differentiation factor 15, and 6-integrin. We also discuss other promising markers, although most of the studies are preliminary and require validation.